A bibliometric and visualization analysis of electrochemical biosensors for early diagnosis of eye diseases - Zhang, Fushen; Xu, Weiye; Deng, Zejun; Huang, Jufang (Frontiers in Medicine, 2025)
Electrochemical biosensors can provide an economical, accurate and rapid method for early screening of disease biomarkers in clinical medicine due to their high sensitivity, selectivity, portability, low cost and easy manufacturing, and multiplexing capability. Tear, a fluid naturally secreted by the human body, is not only easily accessible but also contains a great deal of biological information. However, no bibliometric studies focus on applying electrochemical sensors in tear/eye diseases. Therefore, we utilized VOSviewer and CiteSpace, to perform a detailed bibliometric analysis of 114 papers in the field of research on the application of tear in electrochemical biosensors screened from Web of Science with the combination of Scimago Graphica and Microsoft Excel for visualization to show the current research hotspots and future trends. The results show that the research in this field started in 2008 and experienced an emerging period in recent years. Researchers from China and the United States mainly contributed to the thriving research areas, with 41 and 29 articles published, respectively. Joseph Wang from the University of California San Diego is the most influential author in the field, and Biosensors & Bioelectronics is the journal with the most published research and the most cited journal. The highest appearance keywords were “biosensor” and “tear glucose,” while the most recent booming keywords “diagnosis” and “in-vivo” were. In conclusion, this study elucidates current trends, hotspots, and emerging frontiers, and provides future biomarkers of ocular and systemic diseases by electrochemical sensors in tear with new ideas and opinions.